Design and Assessment of Survey in a 360-Degree Feedback Environment for Student Satisfaction Analysis Applied to Industrial Engineering Degrees in Spain - Francisco-Javier Gr; Ana Isabel Gómez-Merino; Jesús Javier Jiménez-Galea; Isidro María Santos-Ráez; Juan Jesús Fernandez-Lozano; Jesús Manuel Gómez-; Joaquín Ortega-Casanova (MDPI AG, 2023)
The number of students enrolled in engineering studies in Spain is in decline, mainly due to the difficulty in passing the subjects, whose factors may be linked to the science-related content of the subject, a very demanding evaluation system or a lack of active participation of students. The main objective of this study is to provide the student with a 360-degree feedback tool and a survey, from which lecturers can extract the degree of satisfaction of students in its application in a standardized way in scientific-technological activities of BSc/MSc in industrial engineering to quantify learning and motivation. The involvement of students in the assessment process was carried out in three phases: peer-assessment (among students), self-assessment (student himself) and hetero-assessment (teaching staff). After that, a survey was designed, which was validated through confirmatory factor analysis. Ninety-nine percent of the students valued this evaluation experience very positively with respect to the objectivity of the criteria used in the methodology and the material provided by the teaching staff. The fact that only 37.5% of the students considered this experience very favorable for their learning and self-training shows the importance of the teaching staff in their learning process and suggests a need to find complementary improvements to this evaluation system in industrial engineering degrees.